STRATEGI GURU PAI DALAM MENANAMKAN NILAI TOLERANSI BERAGAMA DI SEKOLAH MENENGAH KOTA BINJAI - Indra Satia Pohan; Syahrin Pasaribu; Zailani Zailani; Aisyah Akmalia Fitri (UIN Sumatera Utara Medan, 2025)
This study aims to analyze the strategies used by Islamic Education (PAI) teachers in instilling religious tolerance values in secondary schools in Kota Binjai, identify the obstacles faced during the learning process, and formulate solutions to improve the effectiveness of these strategies. This research employs a qualitative approach with a case study method, involving PAI teachers as research subjects, and data collected through observation, in-depth interviews, and document studies. The results show that PAI teachers apply various strategies such as role modeling, interactive dialogue, and the use of learning media but face challenges including limited time, inflexible curriculum, and negative influences from the social environment and digital media. Proposed solutions include strengthening teacher capacity through training, curriculum reform, support from schools and communities, and utilizing information technology to enhance religious tolerance education.